Bungo Krinok Music from Local to Global - Mahdi Bahar; Hartati M; Indra Gunawan; Fatonah; Uswan Hasan; Zulkarnain (IJCS: International Journal of Community Service, 2023)
Bungo Krinok music is the result of research funded by LPDP for two years (2020 - 2023) in the form of a prototype of a new form of engineered music antithesis to the traditional krinok singing genre of the people of Bungo Regency, Jambi Province. The singing of krinok is accompanied by violin or the supporting community calls piul. The structure of the permanent krinok music composition is used as the main basis and the static framework in music engineering / creation becomes the form (genre) of music composition "Bungo Krinok". Creative and innovative efforts are carried out based on Research and Development methods (Research &; Development = R & D). The creative actions carried out are within the framework of engineering that does not eliminate or coerce certain treatments, thus potentially eliminating or defeating the essential of traditional krinok music itself. His research findings are in the form of a prototype form of Bungo Krinok Music which is implemented in three music models based on the ensemble format, namely the model: Children; Youth, and; Adult. This Bungo Krinok music genre based on local aesthetics is the first step towards the global artistic scene.